Spatial dynamics and driving forces of Asian cities - Yi Jiang (Asian Development Bank (ADB), 2020)
This paper introduces a new city-level panel dataset constructed using satellite nighttime light imagery and grid population data. The dataset contains over 1,500 cities covering 43 economies of Asia and the Pacific from 1992 to 2016. With the dataset, we perform a variety of analyses for Asia and the Pacific as a whole as well as five individual countries in the region. The exercise produces some novel evidence on several interrelated topics including urbanization status and patterns, relations between urbanization and economic growth, evolution of urban systems, primate cities, testing Zipf's law and Gibrat's law, the drivers of city growth, and emergence of city clusters.
Keywords: R11; R12; O18; 330; city cluster; city growth; Gibrat's law; nighttime lights; primate city; Zipf's law